ANALISIS PENGUJIAN PENETRASI PADA LAYANAN HOSTING MENGGUNAKAN METODE BLACK BOX (Studi kasus : Blogspot, Wordpress dan Shared Hosting) - Aditya Bimandaru; Alamsyah, Alamsyah; Nugroho, Aryo (Foristek, 2023)
Analyzing the security of hosting services is important to ensure website security. This research was conducted to test thesecurity level of the Village website. By using 15 samples with 5 websites each, on each Hosting service such as Wordpress,Blogspot, and Shared Hosting. With the Black Box method and Google dork to find the target website to be tested. Open WebApplication Security Project (OWASP) Zed Attack Proxy (ZAP) to find security holes by scanning websites. The resultsobtained are usually 3 types of vulnerabilities, namely Cross Site Scripting (XSS), Cross-Site Request Forgery (CSRF)Tokens, and Clickjacking. After that, analyze the results by seeing how many warnings you get from the scanning process tofind out which hosting service has the highest level of security.This research aims to help the village government build a secure village website. By choosing a safe hosting service andknowing how to find security holes on the website that has been made, so that you can fix these security holes.Keywords : Hosting, OWASP, ZAP, XSS, CSRF.